Human security in world affairs : problems and opportunities - Lautensach, Alexander; Lautensach, Sabina, 1959-; Bellamy, Paul; University of Northern British Columbia; BCcampus; BC Open Textbook Project (University of Northern British Columbia ; BCcampus, 2020)
"This first and only university textbook of human security is intended as an introductory text from senior undergraduate level up includes chapters by 24 authors,from BC, Canada, and around the globe, that encompass the full spectrum of disciplines contributing to the human security field. It is based on the four pillar model of socio-political security, economic security, environmental security and health security. The chapters include learning outcomes, extension activities,and suggested readings; a comprehensive glossary lists key terms used throughout the book. It can be used in courses on international studies and relations, political studies, history, human geography, anthropology and human ecology, futures studies, applied social studies, public health, and more"--BCcampus website.
This work is licensed under the Creative Commons Attribution NonCommercial ShareAlike CC-BY-NC-SA
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from HTML cover (viewed on September 16, 2020).
Keywords: Human security; International relations; Security, International; Human ecology; Climatic changes -- Political aspects; Sustainability; Humanitarian law; Economic security; Human rights; Electronic books